Bird community response to mid‐rotation management in conservation reserve program pine plantations - Lindsey C. Singleton; Brandon G. Sladek; L. Wes Burger; Ian A. Munn (Wildlife Society Bulletin, 2013)
Abstract Open pine–grasslands are one of the most threatened ecological communities in the southeastern United States and provide essential habitat for many regionally declining bird species. While open pine–grassland forests have diminished, acreage of pine plantations has increased throughout the Southeast, in part because of the U.S. Department of Agriculture Farm Bill conservation programs. To understand whether fire and herbicide treatments would be effective in creating pine–grassland structure in plantations suitable for a suite of declining early successional and pine–grassland adapted species, we evaluated combined effects of selective herbicide and prescribed fire on plant and bird communities in thinned, mid‐rotation pine stands established under the Conservation Reserve Program (CRP) in Mississippi, USA. Within each of the 12 replicate sites, we assigned 2 paired 8.1‐ha plots to either treatment (herbicide + prescribed fire) or control in a randomized complete block design. We applied treatments during autumn and winter of 2002–2003. During 2003–2006 breeding seasons, we characterized the bird community using repeated (4–6 repetitions/yr), standardized, 10‐minute point counts from which we estimated species richness, total relative abundance, total avian conservation value, and density of select species. Managed plots exhibited reduced hardwood midstory and a greater abundance of grasses and forbs in the ground layer. Although avian species richness and total relative abundance were similar in treatment and control stands, we observed a shift in the bird community from closed‐canopy forest species to early successional and pine–grassland adapted species, many of which are experiencing population declines. We recommend thinning, hardwood midstory control, and prescribed burning within CRP pine plantations to provide habitat for a suite of regionally declining bird species. © 2012 The Wildlife Society.